A systematic literature review on impact and challenges in the implementation of online learning among accounting teachers and students - Azmi, Nor Idayu; Abdul Kadir, Suhaida; Abdullah, Arnida; Alias, Siti Noormi (Human Resource Management Academic Research Society, 2022)
Teaching and learning utilizing electronic resources has become more prominent. The implementation of online learning in accounting has had an impact and created challenges for students and teachers alike. The purpose of this systematic literature review is to identify the impact and challenges faced by them in implementing online learning of accounting. Surveys on articles were conducted between 2017-2021 using three databases namely ERIC, Mendeley and Scopus. The findings show that online learning had no negative impact on teachers and only shows positive impact in the easy delivery of lessons by teachers. Technology makes the learning process orderly. Positive impact was noted among students too, in terms of improvement in the achievement of the subject and a positive attitude towards it. The negative impact of online learning implementation is that there are students who are stressed because they are less interested in using different learning approaches which slates towards traditional methods. Among the challenges in the implementation of online learning of accounting by students are the lack of technological devices as well as limited access to computers and the internet. While the challenge for teachers lies in the lack of knowledge and skills in executing online learning. Various programmes or workshops need to be designed to enhance skills and improve confidence while implementing online learning of accounting among teachers and students.